Pengaruh Kredibilitas Wartawan, Kualitas Konten, dan Frekuensi Siaran terhadap Tingkat Kepercayaan Publik pada Media Lokal di Jakarta - Youna Chatrine Bchtiar; Luh Putu Widya Adnyani (Journal on Education, 2024)
This research investigates the influence of journalist credibility, content quality, and broadcast frequency on the level of public trust in local media in Jakarta, Indonesia. Data from 200 respondents was analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). The research results show that there is a significant positive relationship between journalist credibility, content quality, and trust in local media. Broadcast frequency also contributes positively, although to a lesser extent. These findings underscore the important role of journalistic integrity and content excellence in fostering public trust in the media. Practical implications for media practitioners include improving journalistic standards and strategic communications strategies to strengthen media credibility and audience engagement in Jakarta.